Antecedents of job satisfaction and organisational commitment - PLS-SEM approach. (5th April 2022) - Khuong, Mai Ngoc; Mai, Tran Phuong; Phuong, Nguyen Thi Minh
This study was conducted in order to identify the relationship between human resource management practices, employee job satisfaction and organisational commitment in hospitality industry in Vietnam. Quantitative approach was mainly applied with exploratory factor analysis, reliability analysis, PLS-SEM using SmartPLS software (version 3.0). The questionnaires were distributed to employees from the lowest level to high-ranked management level. The findings showed that employee organisational commitment was indirectly affected by compensation, career development, leader-follower relationship, working environment and organisational support through the mediation of job satisfaction. In addition, organisation commitment also experienced the direct effect from compensation, career development and leader-follower relationship. Consequently, the result could be recommendations and suggestions for organisation leaders to develop appropriate strategies in order to increase job satisfaction and organisational commitment.